Cost-Effectiveness of Screening for Open Angle Glaucoma Compared With Opportunistic Case Finding. Issue 2 (3rd February 2023) - Anton, Alfonso; Serrano, David; Nolivos, Karen; Fatti, Gianluca; Zmuc, Natasa; Crespo, Carlos; Monleon-Getino, Toni; Sotelo, Katia; Morilla, Antonio; García, Virginia; Comas, Merce; Castells, Xavier
Abstract : Précis: The manuscript evaluates cost-effectiveness of glaucoma screening with imaging devices and telemedicine based on a screening campaign performed in Spain. The screening strategy implemented in our analysis was cost-effective compared with opportunistic case finding. Introduction: Open angle glaucoma is an asymptomatic ocular disease that represents one of the first causes of blindness. Diagnosis is currently made by opportunistic case finding, usually by community optometrists or general ophthalmologists. The aim of this study was to assess the cost-effectiveness of a screening strategy based on optical coherence tomography and fundus photographs in glaucoma detection. Materials and Methods: A cost-effectiveness analysis was carried out to compare 2 alternative strategies: opportunistic finding versus screening. A Markov tree model was carried out with 10 health states according to disease progression. Quality-adjusted life years (QALYs) were used as a measure of effectiveness. We included short-term and long-term direct health costs and a discount rate of 3%. We performed a probabilistic sensitivity analysis and several 1-way sensitivity analyses. Results: The cohort in the screening program entailed an increase in 0.097 QALYs and additional costs of €1187 versus opportunistic finding, with an incremental cost-effectiveness ratio of about €12.214/QALY. The 1-way sensitivity analysis showed that inputs related to age and screening program (cost and detection rate) were those most strongly influencing the results of the analysis. Probabilistic sensitivity analyses showed that the model was robust to significant changes in the main variables of the analysis. Conclusions: The screening strategy implemented in our analysis was cost-effective compared with opportunistic finding in patients with glaucoma in this Spanish setting.